Quantitative PCR for early detection of human cytomegalovirus end-organ disease in immunocompetent host: A retrospective single-center study - Cheon-Hoo Jun; Si-Ho Kim; Junyoung Kim; Kwang Min Kim; Jung Won Lee; Sung Min Kong; Jiyeong Kwak; Byung Soo Kwan; Hyun Kyu Cho; Kyoung-Jin Park; Hyoung Tae Kim; Yu Mi Wi (Elsevier, 2024)
Background: Tissue-invasive end-organ disease (EOD) caused by cytomegalovirus (CMV) is less frequently reported in immunocompetent patients compared to immunocompromised patients. In this study, we investigated the association between CMV viremia and CMV end-organ disease in immunocompetent patients. Methods: Adult patients (≥18 years old) with CMV viremia were screened from January 2010 to June 2022. The primary outcome was the presence of CMV EOD. Risk factors associated with CMV EOD were analyzed, and a receiver operating characteristic curve was plotted to determine the most accurate cutoff value of the CMV titer for the prediction of CMV EOD. Results: Among the 106 immunocompetent patients with CMV viremia, 31 exhibited CMV EOD. Gastrointestinal tract disease was the most common. The log10 value of the CMV titer was significantly associated with the occurrence of CMV EOD in immunocompetent patients with CMV viremia. The optimal cut-off CMV titer for the prediction of CMV EOD was 749 IU/mL. Conclusions: Our study suggests the potential association between high CMV titers and the development of CMV end-organ diseases and describes the diagnostic performance and utility of quantitative PCR as a surrogate marker for predicting the occurrence of CMV EOD in immunocompetent patients.